2021
DOI: 10.1111/ajt.16619
|View full text |Cite
|
Sign up to set email alerts
|

Racial and sex representation in clinical trials: Where are we in abdominal organ transplantation?

Abstract: Clinical trials have historically failed to reflect the diversity of patients who may ultimately benefit from interventions being studied. 1,2 Lack of diversity among trial participants can underestimate the effects of biological variation in treatment effect and further reduce equity and access to evidence-based healthcare for minority patients. 3 The NIH and FDA implemented the Revitalization Act of 1993 to address these issues and provide guidelines to promote the inclusion of women and minorities in clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In this study, we demonstrate better representation of women in kidney transplant trials compared to what has been shown for other medical disciplines, confirming Zaldana et al's earlier findings (9). Overall, we demonstrate a pooled PPR of 0.80 (a PPR of 0.8-1.2 indicates appropriate trial representation) (4, 5) which is significantly better than our earlier examination of the PPR for women in recent non-transplant clinical trials examining medications with important cardiorenal indications (PPR 0.70 for sodium glucose cotransporter-2 inhibitors, 0.72 for glucagon-like peptide-1 receptor agonists, and 0.56 for non-steroidal mineralocorticoid receptor antagonists) (6).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we demonstrate better representation of women in kidney transplant trials compared to what has been shown for other medical disciplines, confirming Zaldana et al's earlier findings (9). Overall, we demonstrate a pooled PPR of 0.80 (a PPR of 0.8-1.2 indicates appropriate trial representation) (4, 5) which is significantly better than our earlier examination of the PPR for women in recent non-transplant clinical trials examining medications with important cardiorenal indications (PPR 0.70 for sodium glucose cotransporter-2 inhibitors, 0.72 for glucagon-like peptide-1 receptor agonists, and 0.56 for non-steroidal mineralocorticoid receptor antagonists) (6).…”
Section: Discussionsupporting
confidence: 91%
“…A recent study published in 2021 examined the PPR for women and minority populations in 172 abdominal transplant trials in the United States from 2000 to 2018. Compared to non-transplant studies where women have been historically and often woefully under included (4,(6)(7)(8), in abdominal transplant trials, women were surprisingly well represented (PPR 0.87) (9). Importantly however, this study did not examine trial characteristics that may have influenced female recruitment.…”
Section: Introductionmentioning
confidence: 86%
“…In addition, for studies that investigated the effect of sex, females tend to be underrepresented 2 . Analysis of clinical trials conducted among kidney transplant recipients in 2000–2018 showed that only 41% of the subjects were females 3 . This review will explore sex‐related biological differences as well as gender‐associated psychosocial factors that exist between males and females, which consequently impact access to kidney transplantation, kidney donation, and kidney allograft and patient outcomes (Table 1).…”
Section: Introductionmentioning
confidence: 99%